Identification of miRNAs and their targets involved in the secondary metabolic pathways of Mentha spp. (October 2016) - Singh, Noopur; Srivastava, Swati; Shasany, Ajit K.; Sharma, Ashok
Graphical abstract: The study revealed that essential oil biosynthesis in Mentha spp. may be governed by miR156, miR414 and miR5021. Three miRNA candidates (miR156, miR5021, and miR5015b) were observed to be involved in trichome development. This is the first in-silico study describing miRNAs and their role in the regulation of secondary metabolic pathways in Mentha spp. Highlights: Eleven miRNAs families and 130 target transcripts were identified. Predicted miRNAs were involved in different metabolic process. miR156, miR414 and miR5021 showed regulation of essential oil biosynthesis. Three miRNAs were involved in trichome development. Abstract: The endogenous, small and non-coding functional microRNAs govern the regulatory system of gene expression and control the growth and development of the plants. Mentha spp. are well known herbs for its flavor, fragrance and medicinal properties. In the present study, we used a computational approach to identify miRNAs and their targets involved in different secondary metabolic pathways of Mentha spp. Additionally, phylogenetic and conservation analysis were also done for the predicted miRNAs. Eleven miRNAs families were identified from Mentha spp., out of which five miRNA families were reported for the first time from Lamiaceae. Overall, 130 distinct target transcripts were predicted for eight miRNAs families. All the predicted targets regulated by predicted miRNAs control the reproduction, signaling, stimulus response, developmental and different metabolic process. miRNA mediated gene regulatory network was also constructed on the basis of hybridized minimum free energy of identified miRNAs and their targets. The study revealed that the gene regulatory system of essential oil biosynthesis may be governed by miR156, miR414 and miR5021 in mint family. Furthermore, three miRNA candidates (miR156, miR5021, and miR5015b) were observed to be involved in trichome development also. This is the first in-silico study describing miRNAs and their role in the regulation of secondary metabolic pathways in Mentha spp.